4044 A Cardiovascular Health and Wellness Mobile Health Intervention Among Church-going African-Americans: Formative Evaluation of the FAITH! App. Issue Volume 4:Issue(2020)Supplement 1 (June 2020) - Brewer, LaPrincess; Kumbamu, Ashok; Smith, Christina; Jenkins, Sarah; Jones, Clarence; Hayes, Sharonne; Patten, Christi A.; Cooper, Lisa A.; Burke, Lora
Abstract : OBJECTIVES/GOALS: To evaluate the FAITH! (Fostering African-American Improvement in Total Health) App mHealth lifestyle intervention by using post-intervention feedback obtained from participants in our intervention pilot study. METHODS/STUDY POPULATION: We used qualitative methods (focus groups) to elicit post-intervention feedback. Participants who completed the pilot study were recruited to one of two focus groups. Semi-structured focus groups were conducted to explore participants' views on the app functionality, utility and satisfaction as well as its impact on healthy lifestyle change. Sessions were audio-recorded, transcribed verbatim and qualitative data were analyzed by systematic text condensation thematic analysis. RESULTS/ANTICIPATED RESULTS: Nine individuals participated (N = 4 and N = 5) in each of the two focus groups. Their mean age was 47.9 years (SD 12.1), 67% were women, and all had at least an education level of some college. Six overarching themes emerged from the data: (1) overall impression, (2) content usefulness (3) formatting, (4) implementation, (5) impact and (6) suggestions for improvement. Underpinning the themes was a high level of agreement that the intervention facilitated healthy behavioral change through cultural tailoring, multimedia education modules and social networking. Among the suggestions for improvement were streamlining of app self-monitoring features, personalization based on individual's cardiovascular risk and attentiveness to nuanced cultural perspectives. DISCUSSION/SIGNIFICANCE OF IMPACT: This formative evaluation found the FAITH! App mHealth lifestyle intervention had high reported satisfaction and impact on the health-promoting behaviors of African-Americans, thereby improving their overall cardiovascular health. The findings provide further support for the acceptability of mHealth interventions among African-Americans. CONFLICT OF INTEREST DESCRIPTION: None.